2009
DOI: 10.1002/cncr.24322
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of molecularly confirmed clear cell sarcoma from a single institution and in comparison with data from the Surveillance, Epidemiology, and End Results registry

Abstract: BACKGROUND: The authors compared disease‐specific survival (DSS) in stage‐specific subgroups of patients with clear cell sarcoma, including those with lymph node metastases (N1M0) and those with distant metastases (N0M1). METHODS: Clinical data regarding soft tissue sarcoma patients were obtained from The University of Texas M. D. Anderson Cancer Center (MDACC) (1980‐2007) and the Surveillance, Epidemiology, and End Results (SEER) registry (1988‐2004). When possible, clear cell sarcoma diagnoses were confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 28 publications
2
4
1
Order By: Relevance
“…The median age of the patients in our study was 41.28 years (range, 6–91 years). Although Kawai et al [19] reported that gender was an independent prognostic factor, previous studies found that gender was not an independent factor for prognosis of CCS [3,12,21]. The findings of these previous studies are consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The median age of the patients in our study was 41.28 years (range, 6–91 years). Although Kawai et al [19] reported that gender was an independent prognostic factor, previous studies found that gender was not an independent factor for prognosis of CCS [3,12,21]. The findings of these previous studies are consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to Blazer et al [21], we found that the majority of patients were diagnosed at an early or localized stage. The 5-year disease-specific survival was 62.9%, and 10-year disease-specific survival was 51.3%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The 5-year survival was 71.4%, which falls within the range reported in the literature and represents an increase in survival over the last decade due to improved diagnostic and therapeutic measures [9]. Tumors with higher grade, increased size, local extension, and metastasis all exhibited lower survival, as expected [10, 11]. Surgical resection is the only curative treatment for sarcoma, and surgical patients had significantly higher survival [3, 12].…”
Section: Discussionmentioning
confidence: 53%
“…However, Black patients and patients from rural areas showed lower 5-year survival when compared to Whites and patients from metropolitan areas, respectively. Further risk-adjusted histology-specific studies are mandated to understand if these differences represent a disparity in access to care among minorities and under-served populations or are a result of differences in histological make-up and tumor behavior in these populations [1, 4, 11].…”
Section: Discussionmentioning
confidence: 99%